MASLAHAH MURSALAH AS A CONSIDERATION FOR COMPLETION OF ISLAMIC LAW BASED ON THE MAQĀṢID SHARĪ`AH PRINCIPLE - Sari, Novita (International Conference on Humanity Education and Society (ICHES), 2024)
Maslahah mursalah is an important concept in Islamic law; in fact, most scholars use maslahah mursalah as a legal istinbat method. In writing this article using a qualitative research method of literature by prioritizing data credibility, the results obtained in this study are that maslahah mursalah has an important role in law. Not even a few Islamic scholars make maslahah murslahah a legal consideration. However, the use of maslahah mursalah is not absolute. To anticipate misuse of maslahah mursalah, maslahah mursalah must meet the requirements that must be considered for legal considerations, such as that it must not conflict with maqāṣid sharī`ah, the scriptures, sunnah, qiyas, maslahah, or a higher level. Maslahah mursalah is an old concept, but it is also very relevant to be applied today by studying Islamic treasures and then applying it in today's life.